The photoacoustic tomographic imaging system based on diode laser and microphone for analyzing healthy and sick colon of broiler - Bonita, Arta Bayti; Wasono, Mohammad Ali Joko; Mitrayana, Mitrayana (AIP Conference Proceedings, 2022)
Research concerned about the analysis of the colon of sick and healthy broilers using a photoacoustic tomographic image system based on a 532 nm green diode laser and a condenser microphone. Photoacoustic tomographic succeeded in imaging sick colon samples with an intensity of -61.4076 dB and healthy with an intensity of -69.9145 dB at a frequency of 17000 Hz and a duty cycle of 40%. The image result of the sick colon is clearer by the dominant colors in red, yellow, and blue, while those for the healthy colon are more dominant in blue and yellow. The image results of the photoacoustic tomographic system were analyzed using ImageJ with the histogram features, profile and surface plot. ImageJ analysis results showed the difference of gray scale level between the colon surface and the colon cavity in the images of a sick and healthy colon. The degree of gray scale in the sick colon is shown higher than that of the healthy colon